2009
DOI: 10.4037/ajcc2009792
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine, Toothbrushing, and Preventing Ventilator-Associated Pneumonia in Critically Ill Adults

Abstract: Background Ventilator-associated pneumonia is associated with increased morbidity and mortality. Objective To examine the effects of mechanical (toothbrushing), pharmacological (topical oral chlorhexidine), and combination (toothbrushing plus chlorhexidine) oral care on the development of ventilator-associated pneumonia in critically ill patients receiving mechanical ventilation. Methods Critically ill adults in 3 intensive care units were enrolled within 24 hours of intubation in a randomized controlled c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
236
1
57

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(297 citation statements)
references
References 33 publications
3
236
1
57
Order By: Relevance
“…In accordance with recommendations 17,18 to prevent VAP, care providers on the unit used an oral care protocol that included an oral chlorhexidine gluconate rinse. [19][20][21] Hospital and university institutional review boards approved the study.…”
Section: Participants and Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with recommendations 17,18 to prevent VAP, care providers on the unit used an oral care protocol that included an oral chlorhexidine gluconate rinse. [19][20][21] Hospital and university institutional review boards approved the study.…”
Section: Participants and Settingmentioning
confidence: 99%
“…Instances in which nurses demonstrated or spoke concretely about oral care problems were written up and circulated to the study team. 21 Then important gaps between standardized ways of speaking or documenting oral care and the unscripted problems encountered by nurses were analyzed. 23 The final analysis involved identifying technical issues and contextual work-arounds to consider opportunities for innovation.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…A escovação dentária do paciente com IOT tem sido objeto de inúmeras pesquisas. 16,17 Estudos têm demonstrado que a utilização de clorexidine é mais importante do que a escovação 17 . Entretanto, sabe-se que a ação dos enxaguantes bucais pode ser comprometida diante de placas de biofilme bucal que são mais bem removidas com as escovas dentárias.…”
Section: Discussionunclassified
“…[8][9][10] The American Association of Critical-Care Nurses has recommended tooth brushing twice daily with a pediatric toothbrush, 11 but clinical evidence that such interventions are well tolerated by patients is lacking. Early studies reported transient but significant increases in ICP of 3-10 mm Hg during unspecified oral care.…”
Section: =4mentioning
confidence: 99%